Physical exercise attenuates stress-induced hypertension in rats but not the impairments on the myocardial mechanics. Issue 3 (March 2022) - Silva, Ariana A.; Perilhão, Mauro S.; Portes, Leslie Andrews; Serra, Andrey J.; Tucci, Paulo Jose Ferreira; Leopoldo, André Soares; dos Santos, Leonardo; Bocalini, Danilo S.
Abstract : Background: Acute and chronic stresses have become a health problem in the contemporary society, and prolonged exposure to stressful events are related to the pathogenesis of cardiovascular diseases. Physical exercise is a well-recognized effective nonpharmacological therapy for cardiovascular diseases and stress-induced injuries. Thus, this study evaluated the effect of exercise on the cardiac remodelling of chronically stressed rats. Methods and results: Wistar adult rats were used ( n  = 10 each group) and chronic stress protocol consisted of restricting movement in individual rodent restrainers (60 min, 5 days/week, 12 weeks); and exercise consisted of swimming sessions in a pool (60 min, 5 days/week, 12 weeks). During protocol, blood pressure was measured in conscious rats, and at the end cardiac morphology/function was assessed. Animals exposed to stress exhibited continuous rise in blood pressure from the sixth week, but exercise attenuated it. Similarly, restrained rats increased serum corticosterone compared with nonstressed rats, but exercise also prevented it. No changes were found in cardiac mass, but chronic stress not only impaired the steady state contractions of the cardiac muscle, but also reduced inotropic responses to stretching, increasing calcium and beta-adrenergic receptor stimulation. Despite this, exercise was unable to prevent these functional impairments induced by stress, and instead, the association of stress and physical exercise worsened myocardial compliance. Conclusion: Despite the known benefits to the cardiovascular system, our results indicate that aerobic swimming exercise for 12 weeks reduced blood pressure but did not impede the chronic stress-induced myocardial damages in rats.